KORUMACILIĞIN GELENEKSEL KENT KÜLTÜRÜNDEN ÇIKARMASI GEREKEN DERSLER SOCIOLOGICAL BACKGROUND IN OUR TRADITIONAL URBAN CULTURE: DISTRICT, STREET AND HOUSES - İsmail DOĞAN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Social habits, values and beliefs effect the other main elements of sedentary culture besides the human behavior and social life. Urban culture and architectural dimensions are at the top of them. The philosophy of social life which takes the big part of its meaning from the world of values determines both architecture which makes the daily life of cities peculiar to a particular culture and also visual dimension. In this axis, it becames inevitable to reach different visual and architectural reality both for Western philosophy considering deepness and expansion in particular residence and area, and for eastern philosophy searching for deepness at the eternity. This is the axis distinguishing Paris from stanbul, Bursa from Parma and Taj Mahal from Western Basilicas.Ottomans are known for an era showing the charasteristics of our traditional culture. Actually, cities like stanbul, Bursa, Edirne, Trabzon, Kayseri, Safranbolu, Baghdad, Bosnia etc. reflect the existing difference in all fields of daily life, from religious to commercial life. Districts, streets and houses are the visible fields of this difference and the sociological background of cities. In this work, these fields are subjected to sociological analysis by acting from the examples of classical period of Ottomans; some suggestions are given for protection of original examples